Pelatihan Perawatan Mesin Bagi Pengelola Bank Sampah Universitas Lancang Kuning - Anto Ariyanto; Guntoro; Hamzah; David Setiawan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Unilak waste bank currently operates three machines: a compost chopper, a press machine, and a plastic chopper. This machine is critical to the operation of the Unilak waste bank, particularly the composting machine. The compost chopper machine is under extreme strain, as it must keep up with the rate of compost production. As a result, it is necessary to conduct training on the proper maintenance of these machines in order to prolong the life of the machines. To address the issue of managing Lancang Kuning University's waste bank, training was conducted using the Learning by Doing method. In general, the participants, particularly the Unilak waste bank manager, were able to absorb and apply general knowledge about machine maintenance.